Malika Muhammada Jāyasī - Bhaṭanāgara, Rāmaratana, 1916- (SAMP early 20th-century Indian books project, 1947)
On the life and works of Malik Muhammad Jayasi, fl. 1540, Awadhi and Hindi poet; includes a brief account of the history of Sufism in India and Sufi literature.